Beyond the operating room: a narrative review of paediatric surgical diseases as a neglected child health priority in low and middle-income countries - Umang Kumar Agrawal; Ambika Kedia (International Journal Of Community Medicine And Public Health, 2026)
Paediatric surgical diseases contribute substantially to childhood morbidity, disability, and mortality worldwide, yet they continue to receive limited attention within public health policies and child health programs, particularly in Low and middle-income countries (LMICs). While remarkable progress has been achieved in reducing deaths from infectious diseases and malnutrition, surgically treatable conditions remain a significant but under-recognized cause of adverse health outcomes among children. Congenital anomalies, acute appendicitis, intestinal obstruction, inguinal hernia, trauma, and surgical infections collectively account for a considerable burden of preventable morbidity and mortality. Delayed recognition, inadequate referral systems, shortage of trained personnel, financial constraints, and geographical barriers often impede timely access to surgical care. Consequently, many children present with advanced disease, resulting in increased complications, prolonged hospitalization, disability, and avoidable deaths. This narrative review examines the burden of paediatric surgical diseases in LMICs, explores major health-system barriers affecting access to care, and highlights their implications for child health outcomes. The review further discusses opportunities for integrating paediatric surgical conditions into existing child health programs and proposes public health strategies aimed at improving access to safe, timely, and affordable surgical care. Recognizing paediatric surgical diseases as a public health priority is essential for strengthening health systems, reducing preventable childhood morbidity and mortality, and advancing progress toward universal health coverage and Sustainable Development Goals.